Pharmacological management of pain during orthodontic treatment: a meta-analysis. - Angelopoulou, M V; Vlachou, V; Halazonetis, D J (Orthod Craniofac Res, 2012)
OBJECTIVES: To evaluate the effectiveness of non-steroidal anti-inflammatory drugs (NSAIDs) in managing pain arising from orthodontic interventions, such as archwire or separators placement. DATA SOURCES: Medline and Cochrane databases searched in February 2010 and updated in July 2010 using orthodontics and pain as the search terms. Additional studies located from Google Scholar, Clinical Trials and the reference lists of retrieved articles. STUDY SELECTION: Randomized controlled trials comparing NSAID to placebo using visual analogue scale (VAS) scores. DATA SYNTHESIS: Of the 1127 studies identified through database searches, seven were included for meta-analysis. Treatment effects (Hedges' g using random effects model) and 95% confidence intervals (CI) of the pain VAS scores were evaluated at 2, 6 and 24 h after intervention, during chewing and biting activities. Pain level at 2 h differed between the ibuprofen and placebo groups during biting (95% CI: -0.178 to -0.046), but not during chewing (95% CI: -0.551 to 0.148). At 6 h, the ibuprofen group exhibited lower pain levels during both activities (chewing 95% CI: -0.640 to -0.123, biting 95% CI: -0.857 to -0.172). At 24 h, no statistically significant difference could be detected between ibuprofen and placebo (chewing 95% CI: -0.642 to 0.112, biting 95% CI: -0.836 to 0.048). No statistically significant difference was found between ibuprofen and acetaminophen at any time point. CONCLUSION: Ibuprofen appears to lower orthodontic pain compared to placebo at 2 and 6 h after separators or archwire placement, but not at 24 h, when pain peaks.
Keywords: Acetaminophen; Anti-Inflammatory Agents, Non-Steroidal; Bite Force; Facial Pain; Humans; Ibuprofen; Mastication; Orthodontic Appliances; Orthodontics, Corrective; Pain Measurement; Randomized Controlled Trials as Topic